2012
DOI: 10.1155/2012/186752
|View full text |Cite
|
Sign up to set email alerts
|

LED Light-Activated Hypocrellin B Induces Mitochondrial Damage of Ovarian Cancer Cells

Abstract: Objective. Hypocrellin is a natural photosensitizer from a traditional Chinese herb. In the present study, our aim is to investigate the effect of LED light-activated hypocrellin B on mitochondria of ovarian cancer cells. Material and Methods. Ovarian cancer HO-8910 cells were incubated with hypocrellin B at the concentration of 2.5 µM for 5 h and then irradiated by blue light from a novel LED source. Cell survival rate of HO-8910 cells was measured using MTT assay 24 h after photodynamic treatment of hypocrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Fu et al 40 first demonstrated that the photodynamic effect of HA could inhibit the mitochondrial ATPase of hepatoma cells in vitro after irradiation by high-voltage sodium light. Moreover, Jiang et al 41 found that hypocrellin B damaged the mitochondrial structure of ovarian cancer HO-8910 cells after PDT. Recently, Zhao׳s group demonstrated that 17-(3-amino-1-pentanesulfonic acid)-substituted hypocrellin B Schiff-base (PENSHB)-mediated PDT decreased the mitochondrial inner membrane potential, subsequently releasing cytochrome c and inducing apoptotic death 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Fu et al 40 first demonstrated that the photodynamic effect of HA could inhibit the mitochondrial ATPase of hepatoma cells in vitro after irradiation by high-voltage sodium light. Moreover, Jiang et al 41 found that hypocrellin B damaged the mitochondrial structure of ovarian cancer HO-8910 cells after PDT. Recently, Zhao׳s group demonstrated that 17-(3-amino-1-pentanesulfonic acid)-substituted hypocrellin B Schiff-base (PENSHB)-mediated PDT decreased the mitochondrial inner membrane potential, subsequently releasing cytochrome c and inducing apoptotic death 42 .…”
Section: Discussionmentioning
confidence: 99%
“…28 Third, the mitochondrion has been reported to play a key role in the regulation of apoptosis. 16,29 Mitochondrial dysfunction including the loss of mitochondrial membrane potential (DCm), permeability transition, and release of cytochrome c from the mitochondrion into the cytosol, are all associated with apoptosis. 30 In this study, the loss of DCm and release of cytochrome c were observed in EAHB-mediated PDT-treated HeLa cells (Fig- that PDT could open the permeability transition pore, which then leads to the loss of integrity of the outer mitochondrial membrane; this would then release the intermembrane proteinssuch as cytochrome c-into the cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, light emitting diodes (LEDs) are becoming more prevalent in a wide application. Due to material advances over the past few decades, efficiencies of LEDs have increased many times [1], and their applications have rapidly grown for automotive taillights, LCD back lights, traffic signals, and electronic signs [2,3]. Moreover, serious greenhouse effect and environmental pollution caused by overusing fossil fuels have disturbed the balance of global climate.…”
Section: Introductionmentioning
confidence: 99%